2021
DOI: 10.3389/fonc.2021.585271
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immune-Inflammation Index and Changes of Neutrophil-Lymphocyte Ratio as Prognostic Biomarkers for Patients With Pancreatic Cancer Treated With Immune Checkpoint Blockade

Abstract: The efficacy of current treatment regimens for pancreatic cancer (PC) remains unsatisfactory. In recent years, immune checkpoint blockade (ICB) therapy has shown promising anti-tumor outcomes in many malignancies, including PC. Inexpensive and readily available biomarkers which predict therapeutic responses and prognosis are in critical need. Systemic immune-inflammation index (SII) and neutrophil-lymphocyte ratio (NLR) are emerging predictors for prognosis of various tumors. We aim to investigate the prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 57 publications
2
38
0
Order By: Relevance
“…The basic characteristics of the included studies are listed in Supplementary Table 1 ; these studies were published from 2019 to 2021. The 11 cohort studies were conducted in China (n=4) [ 12 , 14 , 15 , 17 , 18 ], the Netherlands (n=2) [ 10 ], Austria (n=1) [ 11 ], Italy (n=1) [ 16 ], and the United States of America (USA) (n=1) [ 13 ]. The sample size ranged from 27 to 420, and the total sample size was 2,365.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The basic characteristics of the included studies are listed in Supplementary Table 1 ; these studies were published from 2019 to 2021. The 11 cohort studies were conducted in China (n=4) [ 12 , 14 , 15 , 17 , 18 ], the Netherlands (n=2) [ 10 ], Austria (n=1) [ 11 ], Italy (n=1) [ 16 ], and the United States of America (USA) (n=1) [ 13 ]. The sample size ranged from 27 to 420, and the total sample size was 2,365.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 27 to 420, and the total sample size was 2,365. Nine cohort studies [ 10 14 , 16 , 17 ] were published in English and two [ 15 , 18 ] were published in Chinese. Regarding the study design, nine cohorts [ 10 , 12 – 18 ] were retrospective studies and two [ 11 , 12 ] were prospective studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been studies reporting SII significance in the survival of patients undergoing immunotherapy [26]. Aside from the baseline biomarkers, we believe that the alteration of biomarkers during immunotherapy treatment would provide greater information and indicate an immediate effect from the immunotherapy treatment itself [27]. Shang et al [27] reported that the changes of NLR as prognostic biomarkers for patients with pancreatic cancer treated with immunotherapy in multivariate analysis.…”
Section: Discussionmentioning
confidence: 94%